A PORTRAIT OF TEACHING WRITING IN EFL LEARNERS’ CLASSROOM - Aldha Williyan; Virga Putra Darma (Journal of English Education, 2022)
This paper is designed to assist EFL teachers. It attempts to give insight and share ideas on how four methods of teaching can be implemented in EFL learners’ classrooms, particularly in teaching writing. Audio-lingual, grammar translation, communicative language teaching, and a genre-based approach are among the methods used. Through this study, the teachers can hopefully use the combination of those methods to assist the students in learning writing skills. Audio-Lingual opens the class through drilling activities that are followed by the grammar translation activities. Afterwards, the class continued with the Communicative Language Teaching and the students were eventually assigned to produce a text in the final stage using the Genre Based Approach. To make it clearer, this paper also provides the steps for implementing the combination of the four methods. So, the EFL teachers are able to gain more explicit input.Keywords: audio-lingual, grammar translation, communicative language teaching, and genre based approach